Role of post-translational modifications of Sp1 in cancer: state of the art - Sun, Xutao; Xiao, Chengpu; Wang, Xinyang; Wu, Siyu; Yang, Zhendong; Sui, Bowen; Song, Yunjia (Frontiers in Cell and Developmental Biology, 2024)
Specific protein 1 (Sp1) is central to regulating transcription factor activity and cell signaling pathways. Sp1 is highly associated with the poor prognosis of various cancers; it is considered a non-oncogene addiction gene. The function of Sp1 is complex and contributes to regulating extensive transcriptional activity, apart from maintaining basal transcription. Sp1 activity and stability are affected by post-translational modifications (PTMs), including phosphorylation, ubiquitination, acetylation, glycosylation, and SUMOylation. These modifications help to determine genetic programs that alter the Sp1 structure in different cells and increase or decrease its transcriptional activity and DNA binding stability in response to pathophysiological stimuli. Investigating the PTMs of Sp1 will contribute to a deeper understanding of the mechanism underlying the cell signaling pathway regulating Sp1 stability and the regulatory mechanism by which Sp1 affects cancer progression. Furthermore, it will facilitate the development of new drug targets and biomarkers, thereby elucidating considerable implications in the prevention and treatment of cancer.